A Model of First‐responder Coping: An Approach/Avoidance Bifurcation. (8th August 2016) - Arble, Eamonn; Arnetz, Bengt B.
Abstract: The work of first responders is fraught with numerous stressors, ranging from potentially traumatic critical incidents to institutional strains. The severity and pervasiveness of these difficulties prompt a necessary consideration of the coping methods employed by first responders. The present study developed an empirical model of first‐responder coping strategies, based upon a nationally representative survey sample of 6240 first responders. Participants were drawn from Swedish first responders in the following occupations: coast guard, customs control, military, emergency medical services, fire department and police services. In the final model, exposure to stress related to well‐being through several indirect paths that in sum accounted for the original direct relationship between these constructs. These several indirect paths were classified theoretically as either approach or avoidance coping behaviours or subsequent health outcomes. In general, approach coping behaviours were related to better well‐being; and avoidance was related to a decrease in the outcome. The size of the present sample, as well as the diverse nature of the included first responders, suggests that the resulting model may offer a unique insight into potentially adaptive pathways for first‐responder coping. Copyright © 2016 John Wiley & Sons, Ltd.